2015
DOI: 10.1021/acs.jpca.5b01885
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Studies of the Dechlorination Mechanism of Carbon Tetrachloride on a Vivianite Ferrous Phosphate Surface

Abstract: International audienceChlorinated organics are the principal and most frequently found contaminants in soil and groundwater, generating significant environmental problems. Over the past several decades, Fe-containing minerals naturally occurring in aquatic and terrestrial environments have been used as natural electron donors, which can effectively dechlorinate a variety of chlorinated organics. However, a full understanding of the reaction mechanism of the dechlorination pathway cannot be obtained by experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…Ultrapure water obtained from the ELGA PURELAB Classic system was purged with N 2 for 4 h to prepare deaerated deionized water (DDW, 18 MΩ cm), which was stored in an anaerobic chamber filled with 95% N 2 and 5% H 2 (Coy Laboratory Products Inc.) and used for all the experiments within 3 days. Vivianite was synthesized according to our previously reported method 19 and characterized by X-ray diffraction (XRD), which showed good agreement with the reference data in Joint Committee on Powder Diffraction Standards (JCPDS) (Figure S1).…”
Section: Chemicals and Materialssupporting
confidence: 54%
See 1 more Smart Citation
“…Ultrapure water obtained from the ELGA PURELAB Classic system was purged with N 2 for 4 h to prepare deaerated deionized water (DDW, 18 MΩ cm), which was stored in an anaerobic chamber filled with 95% N 2 and 5% H 2 (Coy Laboratory Products Inc.) and used for all the experiments within 3 days. Vivianite was synthesized according to our previously reported method 19 and characterized by X-ray diffraction (XRD), which showed good agreement with the reference data in Joint Committee on Powder Diffraction Standards (JCPDS) (Figure S1).…”
Section: Chemicals and Materialssupporting
confidence: 54%
“…Recently, a ferrous phosphate mineral, vivianite [Fe II 3 (PO 4 ) 2 ·8H 2 O], has received much attention as a potential reactive Fe­(II)-containing mineral owing to its capacity for adsorption and reduction of arsenic, uranium, cobalt, nickel, and chlorinated organic compounds. , This suggests that vivianite could play a pivotal role in controlling the immobilization of Cr­(VI) in natural and artificial phosphorus-enriched environments under anoxic conditions. However, no systematic research has yet been performed to identify the reaction mechanism for the removal of Cr­(VI) by vivianite.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NZVI can be completely transformed to lepidocrocite in oxygenated water and partially transformed to Fe­(OH) 2 in O 2 -free water in the absence of contaminants . The passivation kinetics and the nature of the products generated have a significant influence on the long-term viability of the technology given that Fe­(II)-containing minerals such as magnetite, vivianite, and green rust and surface-bound Fe­(II) , can further remove organic and inorganic contaminants. In addition, Fe­(III)-containing minerals (e.g., maghemite (γ-Fe 2 O 3 ), goethite and hematite) can effectively remove contaminants via sorptive effects.…”
Section: Introductionmentioning
confidence: 99%
“…Without amino acids, CT is mainly converted to CF, and CT dehalogenation goes via the hydrogenolysis pathway (Figure S1), which means that the trichloromethyl radical (·CCl 3 ) abstracts a proton from sources such as surface Fe–OH 2 + or water to form CF. Lee and his colleagues used density functional theory (DFT) to investigate dehalogenation at the vivianite (Fe 3 (PO 4 ) 2 ·8H 2 O) surface and they demonstrated that ·CCl 3 can abstract a hydrogen from surface water molecules or acquire an electron from the reactive surface to form the trichloromethyl carbene anion (:CCl 3 – ) which can also be protonated in bulk solution to produce CF (Figure S1 and Figure S10).…”
Section: Discussionmentioning
confidence: 99%
“…Stabilization of Carbene Intermediates by Amino Acids: Less CF Formation. Even though amino acids such as GLY, ALA, and SER inhibited CF formation, no significant adsorption of amino acids on the GR Cl surface could be measured at pH 8.0 (Table S1), 30,32 Fe II dissolution from GR Cl demonstrated that amino acids did in fact interact with GR Cl intensively. At pH 8 the net GR particle charge is slightly positive according to the PZC (8−9) measured for similar layered double hydroxides (LDHs).…”
mentioning
confidence: 99%